Integrating perspectives on reasoning about controversial issues: mapping research directions for secondary education - Vandecandelaere, Machteld; Savenije, Geerte; Stoel, Gerhard (Frontiers in Education, 2025)
Reasoning about controversial issues is an essential skill for navigating the complexities of modern society, making its inclusion in secondary education vital. While each discipline and its corresponding school subjects approach controversies through unique content, traditions, and epistemological foundations, significant commonalities also exist. This article builds on insights from a two-day workshop involving five disciplines that explored how controversial issues and related reasoning processes are understood across these fields. Despite disciplinary differences, multiperspectivity emerges as a unifying principle in teaching and learning about controversial issues. The discussion highlights disciplinary approaches to controversial issues and introduces a research agenda inspired by the workshop’s findings. This agenda calls for the development of shared vocabulary, a comparison of design criteria, and deeper insights into the roles of emotions, values and student experiences. By fostering interdisciplinary collaboration, the aim is to enhance teaching strategies and equip students with critical thinking and reasoning skills to address controversial issues effectively.